# Write the Quadratic Equation in General Form and then Choose the Value of "b." (2x - 1)(x + 5) = 0

We will be using the concept of a quadratic equation to solve this.

## Answer: The value of "b" in the equation (2x - 1)(x + 5) = 0 is 9.

Let's solve it step by step.

**Explanation:**

As we all know, an equation of the form ax^{2} + bx + c = 0 (where, a ≠ 0) is know as general form quadratic equation.

Given that, (2x - 1)(x + 5) = 0

2x^{2} + 10x - x - 5 = 0

2x^{2} + 9x - 5 = 0

⇒ a = 2, b = 9, c = -5.